Competitive problem solving and the optimal prize schemes - Toru Suzuki (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Agents compete to solve a problem. Each agent knows own computational capacity as private information and simultaneously chooses either a risky or a safe problem solving method. This paper analyzes the optimal prize schemes from the perspective of the prize designer who wishes to find a solution as quick as possible. It is shown that (i) the winner-take-all scheme can induce excessive risk taking and make problem solving slower (ii) prize schemes with milder competitive pressure induce the optimal risk taking and quicker problem solving.
Keywords: D82; 330; optimal prize scheme; risk taking; problem solving; Wettbewerb; Anforderungsprofil; Ökonomischer Anreiz; Risikopräferenz; Theorie